The Influence of E-Service Quality on Customer Satisfaction of PLN Mobile Users at PT PLN (Persero) ULP Mattoanging - Isnawati; Mawardi; Paramudia (Journal of Business Administration (JBA), 2025)
Importance of digital service quality in the era of globalization is evident from intense competition among companies to provide best service to customers. This research was motivated by several customers who complained about slow loading of website pages and frequent errors in the PLN mobile application. This study aims to find out e-service quality, customer satisfaction, and the Influence of e-service quality on customer satisfaction of PLN mobile users at PT PLN (Persero) ULP Mattoanging. It uses a quantitative approach, with a purposive sampling sample collection technique using hair theory as many as 100 samples that fill out a questionnaire. Data analysis was carried out with SPSS version 30 by conducting validity, reliability, descriptive statistical analysis, normality test, simple linear regression, t-test and determination coefficient. The results of the study showed that the e-service quality at PT PLN (Persero) ULP Mattoanging is very good, the customer satisfaction of PLN mobile users at PT PLN (Persero) ULP Mattoanging is very satisfactory, and e-service quality has a positive and significant influence on the satisfaction of PLN mobile users at PT PLN (Persero) ULP Mattoanging.